Application research on network security operation automation practice based on RPA technology - ZHOU Ying (Dianxin kexue)
The research focuses on the entire lifecycle of networks and information systems, aiming at the full-process scenarios of cybersecurity operations. It establishes a capability framework based on robotic process automation (RPA) technology and adaptive cybersecurity technology, along with address the common pain points in cybersecurity operations, such as high manual dependency, relatively fragmented cybersecurity capability platforms, and missing key points in cybersecurity operations. By constructing an automated cybersecurity operation platform based on RPA technology, the automation transformation of daily cybersecurity work was realized, and the remaining human resources were allocated areas that cannot be automated at the moment, such as business-level cybersecurity analysis, business network security penetration, vulnerability mining, and automated operation script development. Ultimately, it aims to alleviate the contradiction of insufficient manpower, reduce personnel shortages, and improve the coverage and efficiency of cybersecurity work.